2020
DOI: 10.1186/s40560-020-00439-2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic fluid content: a novel parameter for predicting failed weaning from mechanical ventilation

Abstract: Background: Weaning of patients from the mechanical ventilation remains one of the critical decisions in intensive care unit. This study aimed to evaluate the accuracy of thoracic fluid content (TFC) as a predictor of weaning outcome.Methods: An observational cohort study included 64 critically ill surgical patients who were eligible for extubation. Before initiating the spontaneous breathing trial, the TFC was measured using the electrical cardiometry technology. Patients were followed up after extubation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although, in this study no statistically significant differences were identified between the extubation failure and success groups according to the medical diagnosis at admission and to the comorbidities. Some authors ( 25 , 29 - 31 ) observed that sepsis, heart disease, obstructive pulmonary diseases and previous diseases such as cancer, hypertension and stroke were factors significantly associated with the occurrence of extubation failure, which may have not been identified in this research due to the small sample included or the clinical profile of the individuals studied.…”
Section: Discussionmentioning
confidence: 76%
“…Although, in this study no statistically significant differences were identified between the extubation failure and success groups according to the medical diagnosis at admission and to the comorbidities. Some authors ( 25 , 29 - 31 ) observed that sepsis, heart disease, obstructive pulmonary diseases and previous diseases such as cancer, hypertension and stroke were factors significantly associated with the occurrence of extubation failure, which may have not been identified in this research due to the small sample included or the clinical profile of the individuals studied.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, we observed a significant decrease in RR, MAP, SVR, and STR and an increase in TFC, while CO, CI, SV, and SI remained unchanged. TFC is a newer objective parameter that has shown to identify pulmonary congestion which might not be evident on chest x-rays ( 36 , 37 ). One study in critically ill children with respiratory failure and shock demonstrated that high TFC values correlate with pulmonary plethora and predicted patient outcomes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…TFC is a newer objective parameter that has shown to identify pulmonary congestion which might not be evident on chest x-rays ( 36 , 37 ). One study in critically ill children with respiratory failure and shock demonstrated that high TFC values correlate with pulmonary plethora and predicted patient outcomes ( 37 ). Another study in patients with heart failure suggested that TFC may identify patients at risk for decompensation ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokine, such as tumor necrosis factor (TNF), has been shown to contribute to the development of pulmonary edema and alveolar fluid reabsorption [ 9 ]. In addition, thoracic fluid content (TFC) using electric cardiometry has been postulated to provide an estimation of extravascular lung fluid [ 10 ], and TFC correlated well with extravascular lung fluid. TFC could be a useful tool for detecting pulmonary edema in mothers with pre-eclampsia and for diagnosing weaning failure in cardiac patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thoracic fluid content (TFC) using electric cardiometry has been postulated to provide an estimation of extravascular lung fluid [ 10 ], and TFC correlated well with extravascular lung fluid. TFC could be a useful tool for detecting pulmonary edema in mothers with pre-eclampsia and for diagnosing weaning failure in cardiac patients [ 10 ]. However, only a few studies have assessed lung fluid in neonates.…”
Section: Introductionmentioning
confidence: 99%